2006
DOI: 10.1051/forest:2005111
|View full text |Cite
|
Sign up to set email alerts
|

Non-indigenous plant species and their ecological range in Central European pine (Pinus sylvestrisL.) forests

Abstract: -In this study, forest ecosystems were analysed with regard to the occurrence and ecological range of non-indigenous plant species. Pine forests in the NE German lowland, which naturally and anthropogenically occur on a broad range of different sites, were taken as an example. The analysis is based on a data set of about 2 300 vegetation plots. The ecological range was assessed applying Ellenberg's ecological indicator values. Out of a total of 362 taxa recorded in the pine forests, only 12 non-indigenous spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 22 publications
(16 reference statements)
4
25
0
1
Order By: Relevance
“…Together with higher frequency in coniferous tree stands (27/95 vs. 6/56), this may show that C. alternifolia occurs in coniferous tree stands rather than in broadleaved stands, similar to P. serotina . It also confirms observations of Zerbe and Wirth (2006), which found that tree stands of Pinus sylvestris host numerous alien species, including many invasive species. This case may also be considered as an invasional meltdownplantations of ecologically (and mostly also geographically) alien coniferous species facilitate dispersal distance of secondary invaders-P. serotina and C. alternifolia, and both species invade the most invasible stands.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Together with higher frequency in coniferous tree stands (27/95 vs. 6/56), this may show that C. alternifolia occurs in coniferous tree stands rather than in broadleaved stands, similar to P. serotina . It also confirms observations of Zerbe and Wirth (2006), which found that tree stands of Pinus sylvestris host numerous alien species, including many invasive species. This case may also be considered as an invasional meltdownplantations of ecologically (and mostly also geographically) alien coniferous species facilitate dispersal distance of secondary invaders-P. serotina and C. alternifolia, and both species invade the most invasible stands.…”
Section: Discussionsupporting
confidence: 76%
“…Introduction of coniferous species, which are ecologically alien (according to potential natural vegetation) and in most cases geographically alien, is also an introduction of alien species, which resulted in changes of ecosystem properties (transformers sensu Richardson et al 2000). Although we did not measure this transformation, there are a lot of studies describing how coniferous trees planted in habitats of broadleaved forests affect light conditions (e.g., Knight et al 2008;Niinemets 2010;Mueller et al 2016) or soil chemistry (e.g., Binkley and Valentine 1991;Reich et al 2005;Mueller et al 2012), which generally facilitated invasion of alien species (Obidziński and Symonides 2000;Chmura 2004Chmura , 2014Zerbe and Wirth 2006;Paritsis and Aizen 2008). Both species studied coexist in the arboretum, similar to their native range (Burns and Honkala 1990;Coladonato 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Impatiens parviflora is a widely-dispersed therophyte, which is able to invade most forest plant communities (Tokarska-Guzik 2005; Zerbe and Wirth 2006;Chmura 2014). In the study area, I. parviflora occurred in all types of forest plant communities (Ratyńska, 2001;Dyderski and Jagodziński 2014;Dyderski and Wrońska-Pilarek 2015), being a frequent and persistent understory element.…”
Section: Discussionmentioning
confidence: 99%